2012
DOI: 10.1016/j.actatropica.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

The genetic diversity of Plasmodium malariae and Plasmodium brasilianum from human, simian and mosquito hosts in Brazil

Abstract: Plasmodium malariae is a protozoan parasite that causes malaria in humans and is genetically indistinguishable from Plasmodium brasilianum, a parasite infecting New World monkeys in Central and South America. P. malariae has a wide and patchy global distribution in tropical and subtropical regions, being found in South America, Asia, and Africa. However, little is known regarding the genetics of these parasites and the similarity between them could be because until now there are only a very few genomic sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
1
27
0
2
Order By: Relevance
“…Concerning P. brasilianum, it has been demonstrated that monoclonal antibodies against the CSP of this parasite cross-react with those for P. malariae and strong molecular similarities have been described in these species (Cochrane et al 1985, Escalante et al 1998, Yamasaki et al 2011). Accordingly, several authors have suggested host transference of P. simium vs. P. vivax and P. brasilianum vs. P. malariae, although the direction remains unknown (Tazi & Ayala 2011, Guimarães et al 2012). …”
Section: Malaria In the Extra-amazonian (Non-endemic) Regionmentioning
confidence: 99%
“…Concerning P. brasilianum, it has been demonstrated that monoclonal antibodies against the CSP of this parasite cross-react with those for P. malariae and strong molecular similarities have been described in these species (Cochrane et al 1985, Escalante et al 1998, Yamasaki et al 2011). Accordingly, several authors have suggested host transference of P. simium vs. P. vivax and P. brasilianum vs. P. malariae, although the direction remains unknown (Tazi & Ayala 2011, Guimarães et al 2012). …”
Section: Malaria In the Extra-amazonian (Non-endemic) Regionmentioning
confidence: 99%
“…P. brasilianum is closely related to human P. malariae and P. simium is closely related to Old World strains of human P. vivax [48]. Both may reflect a recent anthroponosis, resulting from cross-species transmission of the human parasite to New World Monkeys, but more genetic data is needed before the direction of transfer is substantiated [14], [54], [55]. P. brasilianum is the most generalist mammalian parasite and infects at least 29 species of Atelidae and Cebidae monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…More genetic work on these parasites would help determine the transmission dynamics and whether these species are pan-American or if there are unique lineages within certain hosts or regions. Genetic data will also help uncover the direction of host transfer of these species and how much transmission occurs with humans in the present day [14], [67], [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,63,90 Unique plasmodium-vertebrate interactions continue to be discovered in reptiles and birds. 38,45,49,85,87,120 The earliest genetic evidence of a malaria plasmodium, dated at approximately 30 million years ago, was obtained through the extraction of DNA from mosquitoes fossilized in amber from the Paleogene period.…”
Section: Primate Malariasmentioning
confidence: 99%